Incorporation of a TGF-β2-inhibiting oligodeoxynucleotide molecular adjuvant into a tumor cell lysate vaccine to enhance antiglioma immunity in mice - Tu, Liqun; Wang, Zhe; Yang, Lei; Sun, Xiaomeng; Yao, Yunpeng; Zhang, Peng; Zhang, Xiaotian; Wang, Liying; Yu, Yongli; Yang, Ming (Frontiers in Immunology, 2023)
Introduction Transforming growth factor β2 (TGF-β2), also known as glioma-derived T-cell suppressor factor, is associated with the impairment of tumor immune surveillance. Therefore, blocking TGF-β2 signaling probably be a feasible strategy to develop a novel type of adjuvant for glioma vaccines to enhance antitumor immunity. Methods A TGF-β2 inhibitory oligodeoxynucleotide, TIO3, was designed with sequences complementary to the 3' untranslated region of TGF-β2 mRNA. The expression of TGF-β2 and MHC-I was detected by qPCR, western and flow cytometry in vitro. All the percentage and activation of immune cells were detected by flow cytometry. Subsequently, TIO3 was formulated with Glioma cell lysate (TCL) and investigated for its antitumor effects in GL261 murine glioma prophylactic and therapeutic models. Results TIO3 could efficiently downregulate the expression of TGF-β2 while increase the MHC-I's expression in GL261 and U251 glioma cells in vitro. Meanwhile, TIO3 was detected in mice CD4+ T, CD8+ T, B and Ly6G+ cells from lymph nodes after 24 hours incubation. Moreover, TCL+TIO3 vaccination significantly prolonged the survival of primary glioma-bearing mice and protected these mice from glioma re-challenge in vivo. Mechanistically, TCL+TIO3 formulation strongly evoke the antitumor immune responses. 1) TCL+TIO3 significantly increased the composition of CD4+ and CD8+ T cells from draining lymph nodes while promoted their IFN-γ production and reduced the expression of TGF-β2 and PD1. 2) TCL+TIO3 activated the NK cells with the elevation of CD69 or NKG2D expression and PD1 reduction. 3) TCL+TIO3 increased the glioma-specific lysis CTLs from spleen. 4) TCL+TIO3 downregulated PD-L1 expression in glioma tissues and in Ly6G+ cells among glioma-infiltrating immune cells. Conclusion TIO3 is a promising adjuvant for enhancing TCL-based vaccines to produce a more vigorous and long-lasting antitumor response by interfering with TGF-β2 expression.